Higher education in non-standard wage contracts - Luisa Rosti; Francesco Chelli (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2007)
By applying Markovian analysis to Italian labor market transition matrices we verify whether higher education increases the likelihood of young workers moving from non-standard to standard wage contracts. As we find evidence for the so-called stepping stone hypothesis, we expect graduates to be more likely to pass from non-standard to standard wage contracts than non-graduates, because the signaling effect of education is enhanced by the stepping stone effect of non-standard wage contracts. Nevertheless, we find that non-standard wage contracts of graduates are more likely to be terminated as bad job/worker matches.
Keywords: 330